EXISTENTIAL AND PERSONALITY DIMENSIONS OF A HUMAN BEING (S. KIERKEGAARD, A. LEONTYEV, R. MEY) - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the basic lines of theory of personality of R. Meya are analysed from position of екзистенциальной philosophy.